Does dose reduction of afatinib affect treatment outcomes of patients with EGFR-mutant metastatic non-small cell lung cancer in real-world clinical practice? - Mau, Ern Poh; Chai, Chee Shee; Chong, Kin Liam; Go, Fuang Ho; Yong, Kek Pang; Harissa, Husainy Hasbullah; Lye, Mun Tho; Ibtisam, Muhamad Nor; Kean, Fatt Ho; Muthukkumaran, Thiagarajan; Azlina, Samsudin; Azza, Omar; et al. (AME Publishing Company, 2024)
Background: Afatinib can be started at a dose lower than the recommended starting dose of 40 mg/day for the treatment of epidermal growth factor receptor (EGFR)-mutant non-small cell lung cancer (NSCLC), however treatment outcomes in real-world clinical practice remains unclear. Methods: This retrospective study of patients with NSCLC from 18 major hospitals (public, private or university teaching hospitals) enrolled in Malaysia’s National Cardiovascular and Thoracic Surgical Database (NCTSD) assessed the efficacy of lower doses of afatinib on treatment outcomes in a real-world clinical practice. Data on clinical characteristics, afatinib dosing, and treatment outcomes for patients included in NCTSD from 1st January 2015 to 31st December 2020 were analyzed. Results: Of the 133 patients studied, 94.7% had adenocarcinoma. Majority of the patients (60.9%) had EGFR exon 19 deletion and 23.3% had EGFR exon 21 L858R point mutation. The mean age of patients was 64.1 years and majority (83.5%) had Eastern Cooperative Oncology Group performance status of 2–4 at diagnosis. The most common afatinib starting doses were 40 mg (37.6%), 30 mg (29.3%), and 20 mg (26.3%) once daily (OD), respectively. A quarter of patients had dose reduction (23.3%) due to side effects or cost constraints. Majority of the patients had partial response to afatinib (63.2%) whilst 2.3% had complete response. Interestingly, the objective response rate was significantly higher (72.3%) with afatinib OD doses of less than 40 mg compared to 40 mg (54.0%) (P=0.032). Patients on lower doses of afatinib were two times more likely to achieve an objective response [odds ratio =2.64; 95% confidence interval (CI): 1.20–5.83; P=0.016]. These patients had a numerically but not statistically longer median time to treatment failure (TTF). Median TTF (95% CI) for the overall cohort was 12.4 (10.02–14.78) months. Median overall survival (95% CI) was 21.30 (15.86–26.75) months.